2022
DOI: 10.55606/ijel.v1i2.34
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Science Technology Engineering and Mathematics Approach with Mind Maps on the Higher Order Thinking Skills (HOTS) of Students in Biology Learning Class X SMA N 4 Kerinci

Abstract: This study aims to determine the effect of the mindmap-assisted STEM approach on students' Higher Order Thinking Skills in learning biology class X SMA Negeri 4 Kerinci. This research is experimental research with a group pretest-posttest design model. The population in this study came from students of class X MIPA SMA Negeri 4 Kerinci in the academic year 2021/2022. The research sample was students of class X MIPA 2 and Class X MIPA 4. The sampling technique used was the random sampling technique. The data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The reality of students' 21st century skills in Indonesia is still low. Results can be seen from the results Programme International for Student Assessment (PISA) conducted by the OECD in 2018 concluded that the science literacy of Indonesian students in learning obtained a score of 397, ranked 71 out of 78 countries (Razak et al, 2022;Supriyadi et al, 2023;Utomo et al, 2023;Rahman et al, 2023). The results are supported by the results of the TIMSS study In 2015, the critical thinking skills of Indonesian students in science and mathematics were ranked 41 out of 48 member countries (Son et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The reality of students' 21st century skills in Indonesia is still low. Results can be seen from the results Programme International for Student Assessment (PISA) conducted by the OECD in 2018 concluded that the science literacy of Indonesian students in learning obtained a score of 397, ranked 71 out of 78 countries (Razak et al, 2022;Supriyadi et al, 2023;Utomo et al, 2023;Rahman et al, 2023). The results are supported by the results of the TIMSS study In 2015, the critical thinking skills of Indonesian students in science and mathematics were ranked 41 out of 48 member countries (Son et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Students' creative thinking skills in learning are still relatively low (Herdiawan &;Langitasari, 2019;Putra et al, 2023;Vishnu et al, 2014). Based on the results of PISA in 2018, Indonesian students' creative thinking skills and science literacy are still low, obtaining a score of 396, ranking 71 out of 79 participating countries (Suharyat et al, 2022;Razak &;Oktarina et al, 2021;Suhaimi et al, 2022;Elfira et l., 2023;Sofianora et al, 2023). In teacher learning activities, students do not involve active and creative students in learning (Syafrial et al, 2022;Taş &;Minaz, 2022;Winarto et al, 2022).…”
Section: Introductiommentioning
confidence: 99%
“…The era of the industrial revolution 4.0 has had a great influence on the development of the world of education (Razak et al, 2022;Priyanto, 2020). The world of education today has utilized technology and information that supports the learning process.…”
Section: Introductionmentioning
confidence: 99%